Le journal comme palimpseste ? Une hypothèse sur l’hétérogénéité de la poétique flaubertienne dans Bouvard et Pécuchet - Laure Demougin (Flaubert: Revue Critique et Génétique)
When he was writing Bouvard et Pécuchet, Flaubert used books much more than newspapers, which were more repulsive objects than a source of inspiration. Despite this fact, and in addition to the claimed influence of the encyclopedia, the very functioning of the novel suggests a polyphony which may lead to a journalistic influence, for example when it comes to the succession of discoveries – which can remind us of the newspaper’s headings. Assuming the presence of the newspaper in Bouvard et Pécuchet and reading the text from this prospect leads to focusing in particular on the character of Gorgu : in this paper, we aim to study Gorgu from the angle of a media poetics into the initial diegesis.